Isthilâh Al-Insân fi Sûrah al-Isrâ’ ’Inda Ibn ‘Asyur fi Kitâb At-Tahrîr Wa At-Tanwîr - Ahmad Fadly Rahman Akbar; Andrayu Muana (Universitas Darussalam Gontor, 2018)
Many of the scientists and scholars who examine and explore the human as a unity from all sides. Some scientists pay attention to the scientific side and the others examined in terms of the language contained in the Qur'an. The famous exegetes with the language method he uses in interpreting the word in the Qur'an is Imam At-Thahir Ibn Aysur who wrote the phenomenal exegetical book in his linguistic explanation called